2018
DOI: 10.1016/j.jamda.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Decision Tool for the Empiric Treatment of Suspected Urinary Tract Infection in Frail Older Adults: A Delphi Consensus Procedure

Abstract: A decision tool for suspected UTI in frail older adults was developed based on consensus among an international expert panel. Studies are needed to evaluate whether this decision tool is effective in reaching its aim: the improvement of diagnostic evaluation and treatment for suspected UTI in frail older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 30 publications
2
63
0
1
Order By: Relevance
“…PALTC settings are recommended to adapt one of the published clinical algorithms to guide the diagnosis and decision to initiate antibiotics for residents with a suspected UTI. 12,15,19,20 y When choosing an antibiotic agent, clinicians will also need to consider additional factors including (but not limited to) resident allergies, co-morbidities, potential drugdrug interactions, availability, local resistance pattern/urine culture results, cost, and overall clinical status. Similarly, final treatment duration will also depend on overall clinical condition and response to the treatment.…”
Section: Diagnosis Of Utismentioning
confidence: 99%
See 1 more Smart Citation
“…PALTC settings are recommended to adapt one of the published clinical algorithms to guide the diagnosis and decision to initiate antibiotics for residents with a suspected UTI. 12,15,19,20 y When choosing an antibiotic agent, clinicians will also need to consider additional factors including (but not limited to) resident allergies, co-morbidities, potential drugdrug interactions, availability, local resistance pattern/urine culture results, cost, and overall clinical status. Similarly, final treatment duration will also depend on overall clinical condition and response to the treatment.…”
Section: Diagnosis Of Utismentioning
confidence: 99%
“…z More recently published criteria usually define fever as single oral temperature of !100 F, or repeated oral temperatures of >99 F, or increase in temperature of !2 F over baseline. 12,15,19,20 emergency department, the authors identified 19 cases of UTI. From the same cohort, emergency department physicians identified 24 cases whereas the Loeb minimum criteria and CDC surveillance definitions detected 13 and 5 cases, respectively.…”
Section: Diagnosis Of Utismentioning
confidence: 99%
“…40 The focus of ongoing research efforts includes the evaluation of diagnostic point-of-care biomarkers (C-reactive protein and procalcitonin) and the implementation of a decision tool for the treatment of urinary tract infections (UTIs). 41 In 2015, the Dutch Minister of Health launched a national action plan on antibiotic resistance. This action plan comprises a One Health approach, covering multiple sectors (ie, human medicine, veterinary medicine, livestock production, food safety, public health, and environmental sciences).…”
Section: The Netherlandsmentioning
confidence: 99%
“…29 Additionally, opinions are prevalent among many nurses and providers that are unsupported by the scientific literature but lead to antibiotic overuse; examples include belief that changes in urine color or odor merit antibiotic treatment, 33 that asymptomatic bacteriuria should be treated, 34 and that nonspecific status changes, such as weakness or decreased oral intake, should be considered a UTI until proved otherwise. 29,35 To address these issues, several expert panels have developed consensus standards for diagnosis of UTI, 36,37 and to identify when antibiotic use is appropriate. 38,39 Most notable are the criteria of Loeb et al, 38 which are for antibiotic initiation, and the criteria of McGeer, 39 which were designed for retrospective surveillance.…”
Section: Discussionmentioning
confidence: 99%